PENERAPAN PERMAINAN SHIRITORI DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG - LARASATI, DINAR (HIKARI, 2020)
Abstract The study aims to examine the results of the study, regarding the application of the Shiritori games used in learning Japanese vocabulary, the results of Shiritori games and the response of teachers and students to the game Shiritori in the learning of Japanese vocabulary, with the main purpose of this research try to provide solutions conceptually about alternatives to other game techniques in learning Japanese vocabulary. The results of the study of the results are as follows: 1) The steps of the game Shiritori in Japanese language learning, including: preparatory stage and implementation of group learning; 2) The implementation of the game in vocabulary learning greatly contributes to changes in students attitudes and behaviors, i.e. (1) Motivating students so that they play an active role and have an interest in the learning process. (2) Facilitate students in remembering vocabulary. (3) Training students concentration so as to think quickly. (4) The game can build a sense of responsibility of students. (5) Shiritori games can build interest and learning motivation (6) reducing gaps between students and teachers. (7) Effective games improve student vocabulary; While 3) difficulties or constraints experienced by teachers in the study of Japanese vocabulary is a constraint in class management. The solution the author proposed in this study was the use of game techniques by applying Android-based shiritori games. Hopefully through the utilization of ICT devices, learning Japanese vocabulary is more practical. In addition, teachers can direct students using gadgets not only to play social media but also to learn. Keywords: shiritori games, Japanese vocabulary, Android based games?? ?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????:1)???????????????????:???????????????2)?????????????????????????????(1)??????????????????????????????????????????????(2) ?????????(3) ??????????????????? (4) ???????????????????????(5)????????????????????????(6)?????????????????(7)??????????????????????3)??????????????????????????????????????????????????????????????????????????????????????????????????ICT?????????????????????????????????????????????????????????????????????????????????????????????????????? ?????: ???????, ?????, ?????????????